Execution of Requesting a Document or Information from Computer data by Defence Party - Giorgi Latsabidze (European Scientific Journal, ESJ, 2023)
The purpose of this investigation was to determine whether the principle of equality and adversarial proceedings is genuinely protected when a lawyer files a motion with a court. The court is then granted the right to request documents or information from both the prosecution and the defense. However, there is concern that the prosecution, in enforcing the law, may contain a flaw that threatens to violate the principles of adversarial proceedings and equality between the parties. On May 24, 2022, the Criminal Procedure Code of Georgia (hereafter – GCPC) was amended. With a motion to request documents or information, the court can now apply to both the prosecution and the defense parties. Nevertheless, the concern remains that the prosecution's enforcement of the law may create an imbalance, jeopardizing the principles of adversarial proceedings and equality. This amendment extends the general rule of conducting investigative actions to include the request for documents or information. Consequently, the rules governing the execution of such requests have also undergone changes. The paper will examine the court's practices and conclude whether the principles of equality of arms and adversarial proceedings are violated.